2005
DOI: 10.1097/01.btf.0000163588.52464.78
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term (10 to 14 Years) Results of the Ramses Total Ankle Arthroplasty

Abstract: n ABSTRACTFrom 1989 until the end of 1993, 73 Ramses Total Ankle Arthroplasty (Ramses TAA) procedures were performed by the surgeons of the Talus Group. It was the beginning of our experience with this implant. We evaluated the long-term clinical results in 69 cases, after 10 years to 14 years postoperatively. Out of 57 cases the result was good for 40 cases, fair for 14 cases, and poor for 3 cases. Arthroplasties were considered to be a failure with removal of the implant and arthrodesis done in 7 cases: 4 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Currently, a number of long-term studies have demonstrated acceptable clinical results, with decreased pain and improved function status. 12,42,44,45,58,78 These results have revived the optimism for total ankle arthroplasty. The absence of hindfoot and midfoot arthritis noted in one study may be particularly encouraging.…”
Section: Arthroplastymentioning
confidence: 99%
“…Currently, a number of long-term studies have demonstrated acceptable clinical results, with decreased pain and improved function status. 12,42,44,45,58,78 These results have revived the optimism for total ankle arthroplasty. The absence of hindfoot and midfoot arthritis noted in one study may be particularly encouraging.…”
Section: Arthroplastymentioning
confidence: 99%
“…A total of about 350 Ramses prostheses have been implanted by the inventors' group. 98 The results can only be retrieved from the New Zeeland Joint Arthroplasty Register 57 (Table 5).…”
Section: Part 2: Designs Presently In Usementioning
confidence: 99%
“…The results published by the developers of the prosthesis refer to the cemented version used before 2000. A 17.4% failure with 39% radiographic loosening rates, after more than 10 years of follow-up, 98 has probably caused the turn towards non-cemented fixation since 2000.…”
Section: The Ramses Prosthesismentioning
confidence: 99%